PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS ICT DAN GAYA BELAJAR TERHADAP HASIL BELAJAR IPA DAN KETERAMPILAN BERTANYA SISWA SD NEGERI 060798 MEDAN AREA - Siti Zahara Harahap; Ulfah Sari Rezeki (JURNAL CURERE, 2019)
This research aims to find out: (1) Differences in student learning outcomes taught using Camtasia media with conventional media; (2) Differences in student learning outcomes that have visual, auditory and kinesthetic learning styles taught by Camtasia media; and (3) Differences in student learning outcomes that have visual, auditory and kinesthetic learning styles that are learned with conventional media. The population in this study was grade V students of SD Negeri 060798 Medan Area, amounting to 82 students consisting of 3 classes. While the study sample is all 3 classes. The research instrument was in the form of a science learning outcomes test, and a learning style questionnaire. This research method is quasi-experimental hypothesis analysis technique t test; and analysis of variance. The results showed that: (1) Student learning outcomes taught with Media Camtasia 85.26 ± 5.45 (± SD) were higher than learning with conventional media 75.52 ± 5.86 (tcount = 8.147; p = 0.000); (2) There are differences in student learning outcomes that have visual, auditory and kinesthetic learning styles that are learned with Media Camtasia (Fcount = 24,964; p = 0,000); (5) there are differences in student learning outcomes that have visual, auditory and kinesthetic learning styles that are learned with Conventional media (Fcount = 6.770; p = 0.002).